Glycerol monolaurate ameliorates DSS-induced acute colitis by inhibiting infiltration of Th17, neutrophils, macrophages and altering the gut microbiota - He, Ke-Jie; Dong, Jia-Hui; Ouyang, Xiao-Mei; Huo, Ya-Ni; Cheng, Xiao-Shen; Lin, Ying; Li, Yue; Gong, Guoyu; Liu, Jingjing; Ren, Jian-Lin; Guleng, Bayasi (Frontiers in Nutrition, 2022)
ABSTRACT Background and Aims Inflammatory bowel disease (IBD) places a heavy medical burden on countries and families due to repeated and prolonged attacks, and the incidence and prevalence of IBD are increasing worldwide. Therefore, finding an effective treatment is a matter of great urgency. Glycerol monolaurate (GML), which has a twelve-carbon chain, is a compound naturally found in human breast milk. Some studies have shown that GML has antibacterial and anti-inflammatory effects. However, the specific mechanism of action remains unclear. Methods Acute colitis was established in mice using 3% DSS, and glycerol monolaurate (500 mg·kg−1) was administered for two weeks. QPCR and western blotting were performed to examine the inflammatory status. Mice described were subjected to flow cytometry analysis for immune cell activation. Results GML treated alleviated macroscopic symptoms such as shortened colons, increased spleen weight, and caused weight loss in mice with DSS-induced colitis. In addition, GML decreased the expression of pro-inflammatory factors (NF-α, IL-1β and IL-1α) and increased the expression of anti-inflammatory factors (IL-10 and TGF-β). GML inhibited the activation of the MAPK and NF-κB signalling pathways, improved tissue damage, and increased the expression of intestinal tight junction proteins. In addition, LPMCs extracted from intestinal tissue via flow cytometry showed that GML treatment led to a decrease of Th17 cells, Neutrophils and Macrophages. 16S rDNA sequencing showed that GML increased the abundance of commensal bacterium such as Akkermansia and Lactobacillus murinus. Conclusions We showed that oral administration of GML ameliorated DSS-induced colitis by inhibiting infiltration of Th17 cells, Neutrophils, and Macrophages, protecting the intestinal mucosal barrier and altered the abundance of commensal bacterium. This study provides new insights into the biological function and therapeutic potential of GML in the treatment of IBD.